The Influence of Age And Technology on The Absorption of Students In Acquiring Language (English Language) - Munira (CV. Arunika Media Nusantara, 2025)
This study, entitled The Influence of Age and Technology on Students’ Language Acquisition Absorption, examines how age factors and the use of technology contribute to improving students’ absorptive capacity in language learning. The primary focus of this research is to analyze the extent to which learning technology and age differences influence students’ ability to understand, retain, and effectively use linguistic information. The objective of the study is to determine the impact of these two variables on students’ absorptive capacity, particularly in the context of language learning, which involves cognitive, affective, and interactive processes simultaneously. This research employed a qualitative approach using descriptive qualitative data analysis techniques. This method was chosen to describe the real conditions occurring in the field based on observed learning phenomena. Data were collected through observations of the learning process, students’ interactions with technological media, and their responses in understanding language materials. The analysis was conducted by interpreting patterns of learning behavior, levels of student engagement, and the ease of access to information provided by learning technologies. The findings reveal that the use of technology in the learning process has a more significant influence on students’ absorptive capacity compared to learning without technological support. Technology enables students to access materials before class, review content anytime, and understand concepts through more engaging visual and interactive media. In addition, age is also an important factor; younger learners tend to have higher absorptive capacity due to greater cognitive plasticity. Therefore, the integration of technology and an understanding of age-related learning characteristics are strategic factors in enhancing the effectiveness of language learning